Self-Disclosure Students Reveal Problem in Individual Counseling Services - Alam Nasyar; Riska Ahmad (Universitas Negeri Padang, 2020)
In the counseling process ideally students are open in presenting their problems. But on the fact that the students is less open in expressing problems to the teachers of guidance of counseling. Therefore individual counseling services are the right choice in expressing the problems experienced by students at school. Through individual counseling students are open and can feel how to know themselves and help develop their potential. This article is a literature study that will explain the students' self-disclosure about problems in individual counseling services. The results of the literature review obtained under self-disclosure become one of the important things that must exist in the implementation of counseling, because self-disclosure as one indicator of closeness and disclosure of personal information as an individual's need to obtain solutions to the improvements made in each.